Erosive wear of natural gas pipes due to high velocity jet impact: Computer simulation study - Majid Z.A.; Mohsin R.; Yusof C.M.Z. (Penerbit UTM Press, 2023)
A sequential failures of underground API 5L X42 carbon steel and the SDR 17, 125 mm polyethylene pipes placed side-by-side to a water pipe was studied. Previous study shown that high pressure water jet from leaked water pipe that had mixed with surrounding soil formed water soil slurry with high erosive properties had severely impacted on the pipe surface causing the loss of pipe coating materials. This phenomenon eventually causes rapid thinning of the steel pipe body which later led to its failure. In this study Computational Fluid Dynamics (CFD) and structural analysis were performed to simulate numerically the chronological event of pipeline failure, in comparison with the findings made in the previous study. The structural and CFD simulation results proved that the location, rate and the extent of erosion failures on the pipe surfaces can be well predicted, as compared with actual instances. Penerbit UTM Press, Universiti Teknologi Malaysia.